Propagation and variability of the yeast [PSI+] prion - Ter-Avanesyan, Michael (Henry Stewart Talks, 2008)
Prion, Yeast prions as non-chromosomal genetic determinants, Modular structure of the Sup35 protein responsible for the yeast [PSI+] prion, Role of the Hsp104 chaperone in [PSI+] prion propagation, Two-level structure of the [PSI+] prion aggregates and methods for studying the size of prion polymers, Non-prion amyloids in yeast, Variability of the yeast [PSI+] prion
Archived at 2021/02/25